A Review On Comparing Extension Programme Streams: When And How To Execute Them - Azizah, Siti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2008)
The article aims to compare some streams of extension by describing their ospects, objectives and how they work in practice. Streams of extension proposed by Fell (1997), Coutts and Roberts (2003) and Roling (1995) were compared to get some understanding about in what situation and how suppose to execute the right stream (s) in such condition. Extension officers and decision makers in the extension field should consider those comparisons since some streams might be more useful when they are combined together to fill some weaknesses with others' strengths. In the last section, a local example of the application of extension streams combination in Indonesia is demonstrated to give clear explanation for readers